Crime and poetry - Flower, Amanda (Flower, Amanda. Magical bookshop mystery., 2016)
Violet Waverly rushes home to her ailing grandmother to find it was all a ploy to get her closer to home. Violet begins working in Charming Books, her grandma's magical bookshop. Soon a dead man is discovered clutching a volume of Emily Dickinson's poems and Violet is caught up in the mystery.